Dinamika Kelompok Usaha Bersama “Mina Jaya” di Desa Puger Kulon, Kecamatan Puger, Kabupaten Jember - Dyah Ayu Roro Kiswari; Sri Subekti (AGRITEXTS: Journal of Agricultural Extension, 2024)
A group can be considered to be developing if it is capable to make improvements in responding to changes that occur within the group itself, such as the phenomenon that occurred in Mina Jaya Joint Business Group (KUB) in Puger Kulon Village, Puger Sub-district, Jember Regency. This study aims to analyze the dynamics of the Mina Jaya KUB group. The study used a qualitative approach. Data collection was carried out through in-depth interviews, observations, and documentation. Research informants were selected using the purposive method. The analysis used the Miles & Huberman analysis model. The results of the study indicate that the dynamics of Mina Jaya KUB are considered dynamic based on the elements of group dynamics. The group’s objectives are to serve as a platform for the learning process, a venue for cooperation, an organization for joint activities, and self-reliance. The group members were able to explain and understand the group’s objectives, making the objectives effective. The group’s structure consists of a chairman, secretary, treasurer, supervisor, members, and advisor. Each role has been carried out according to the group’s task functions, including coordination, providing information, taking initiatives, ensuring member satisfaction, explaining, and disseminating information. The group regularly conducts monitoring and evaluation at each meeting and makes efforts to increase participation by fostering communication and providing rewards. Group members do not have specific intentions for their participation in the group.